Impact of Ag-Doped on the Ferromagnetic-Metallic Transition in Pr0.75Na0.25mno3 Manganites - Khairulzaman, N; Ibrahim, N; Shamsuddin, S (International Journal of Engineering and Technology, 2018)
Monovalent doped Pr0.75Na0.25-yAgyMnO3 (y = 0–0.10) manganite have been investigated using X-ray diffraction (XRD) and scanning electron microscope (SEM) as well as DC electrical resistivity and AC susceptibility measurement to clarify the influence of Ag- doped on charge ordering (CO) state. XRD analysis revealed all samples consists of essentially single phase and crystallized in an orthorhombic structure with space group Pnma. SEM images of Pr0.75Na0.25-yAgyMnO3 compound shows the successful substitution of Ag+ ions with the enhancement of the grains boundaries and sizes as well as the compaction of particles. On the other hand, resistivity and susceptibility measurements showed that the y = 0 sample exhibits insulating behavior and anti-ferromagnetic. Interestingly, the ferromagnetic-metallic transition was observed for y = 0.05 due to the revival of double-exchange (DE) mechanism as a result of weakening the Jahn-Teller effect which caused the CO state to be weakened. However, increasing of Ag-doped up to y = 0.10 induce back its transition into anti-ferromagnetic insulating behavior suggestively due to the weakening of DE mechanism.